Water Savings and Performance of ‘KSUZ 0802’ Hybrid Zoysiagrass in Response to Irrigation Strategy - Manoj Chhetri; Jack D. Fry; Megan M. Kennelly; Dale J. Bremer; Ambika Chandra (HortTechnology, 2023)
Irrigation methods that can minimize water use are needed, and the performance of recently released ‘KSUZ 0802’ hybrid zoysiagrass (Zoysia matrella × Zoysia japonica) has not been evaluated under such management. Therefore, field experiments were conducted in Manhattan, KS, and Dallas, TX, USA, to compare the amount of water applied and ‘KSUZ 0802’ performance and recovery resulting from irrigation using the following: 1) routine irrigation (1.2 inches/week), 2) evapotranspiration (ET)-based irrigation (60% of reference ET), 3) soil moisture sensor (SMS)-based irrigation, and 4) no irrigation. The experiment was conducted under a rainout shelter in Kansas from 15 Jul to 27 Sep 2019 and 8 Jun to 19 Oct 2020, and in Texas the experiment was conducted under open field conditions from 22 Jun to 9 Sep 2020. The SMS-based irrigation method in Kansas reduced water application by 68% and 52%, respectively, compared with routine or ET-based irrigation. In Texas, the corresponding water savings were 29% and 13%, respectively. The water savings discrepancy was mainly due to differences in local weather conditions and irrigation demand. Visual turf quality of turf receiving SMS-based irrigation remained above the minimally acceptable level throughout the study in Kansas, whereas in Texas, turf quality declined below acceptable level after 2 weeks. In Kansas, turf retained acceptable quality for more than 21 days with no irrigation, and after rewatering, nonirrigated turf recovered back to significant green cover (93% in 2019 and 67% in 2020). ‘KSUZ 0802’ demonstrated good drought tolerance and recovery in Kansas.